Action learning and action science: Are they different? - Joseph A. Raelin (Organizational Dynamics, 1997)
Kurt Lewin's referral to action research as a way to conduct systematic inquiry into group phenomena gave rise to the so-called 'action technologies.' Two of the most popular action technologies that emerged from action research are action learning and action science, both of which seek to help individuals by making them become more effective in achieving useful action. While action learning operates within the framework that people learn most effectively when working on real-time problems that occur in their own work setting, action science is based on the notion that people can improve their interpersonal and organizational effectiveness by examining the latent beliefs that spur their actions. Organization development facilitators must strive to examine both technologies for them to better understand respective methods and their possible effects.
Keywords: D73; M10; M12; M53; O15; 330; Action learning; Action science; Facilitation; Learning; Organization development; Leadership development